(untitled) (Scientific journal of the Fergana State University, 2023)
The article aims to research the emergence and historical evolution of ideas and views on civil society in Central Asia in a socio-philosophical way. The authors tried to substantiate the ijtimi-political views of the great ancient scholars of Central Asia, including: Abu Nasr Farabi, Ibn Sina, Alisher Navoi and state and public figures Amir Temur, on the need for today’s study.